Development and Validation of a Pioneer Scale on Service Leadership Behavior in the Service Economies - Shek, Daniel T. L.; Dou, Diya; Ma, Lawrence K. (Frontiers in Psychology, 2019)
In response to the severe lack of leadership assessment tools in the Chinese context, the Service Leadership Behavior Scale was developed based on the Service Leadership Model proposed by Po Chung, the co-founder of DHL International. Utilizing responses from 4,486 Hong Kong undergraduates, this paper reports the findings of a validation study on the Short-Form Service Leadership Behavior Scale (SLB-SF-65). Previous findings based on exploratory factor analysis revealed a six-factor 48-item solution (SLB-SF-48). With the removal of ten items, confirmatory factor analysis showed that the final 38-item scale (SLB-SF-38) possessed excellent psychometric properties and factorial stability based on multigroup invariance analyses. The SLB-SF-38 also exhibited excellent reliability and convergent validity. Overall speaking, the present study underscored the utility of the SLB-SF-38 as an objective assessment instrument of service leadership behavior in the education, research and personnel training contexts.